Olfactory perception and wellbeing across hormonal contraceptive users and menstrual cycle phases - Gonçalves, Patrícia Maria Rodrigues; Azevedo, Bruna Cestari de; Fomin, Denilson; Galeazzo, Raul Galliano; Veiga, César Antônio; Rezende, Natália Queiroz; Siba, Isadora Pozzetti; Pascarelli, Raphaela Goncalves Barros; Dieamant, Gustavo; Podgaec, Sérgio; Pinheiro, Camila Hernandes (Frontiers in Human Neuroscience, 2026)
Hormonal fluctuations are known to influence olfactory performance, but the effects of oral contraceptive (OC) use remain unclear. This study examined 98 women aged 18–40, including OC users and naturally cycling women, using the Sniffin’ Sticks test—a standardized assessment of olfactory threshold, discrimination, and identification—and self-report measures of life satisfaction and subjective happiness to capture emotional factors linked to olfaction. All participants were evaluated at two standardized time points: for naturally cycling women, during the periovulatory and luteal phases; for OC users, during the corresponding active and inactive phases of the pill cycle; and for continuous users, at matched intervals. OC users were categorized by hormonal formulation (ethinylestradiol 0.02 mg, ethinylestradiol 0.03 mg, estradiol valerate, or progestogen-only pills) and regimen (cyclical or continuous). No overall differences in olfactory performance were found between OC users and non-users. Exploratory analyses indicated that women using estradiol valerate-based oral contraceptives tended to show higher threshold and TDI scores compared to other regimens, a pattern that warrants further investigation given the limited sample size (n = 4). Lower olfactory performance was also associated with progestogen-only formulations and continuous OC use, and longer OC use duration was negatively associated with threshold sensitivity. Across all groups, better olfactory performance was related to higher subjective wellbeing in both OC (n = 47) and NOC (n = 51) groups. By examining specific contraceptive types and incorporating emotional wellbeing as a variable, this study contributes new insights into the complex relationships between hormonal status and sensory-emotional functioning. Overall, these preliminary findings suggest that contraceptive formulation, regimen, and emotional state may be linked to variability in olfactory processing, highlighting underexplored associations that may inform future research on hormonal contraception and sensory-emotional functioning.